Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Pemahaman Akuntansi Pada Mahasiswa Kota Batam - Edi Susanto; Dian Efriyenti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to investigate the elements that impact the understanding of accounting.., Utilizing a quantitative methodology, this study aims to thoroughly examine the effects of the dependent variables. Namely intellectual intelligence, emotional intelligence, and spiritual intelligence, on the independent variable, which is accounting understanding. The research was conducted in Batam City, with the study population comprising accounting students from Batam International University (UIB), Universal University (UVERS), and Batam State Polytechnic (POLTEK). The analytical method employed was multiple regression, facilitated by the SPSS V25. The findings for this study revealed that the intellectual intelligence variable exhibited a positive yet nonsignificant influence on accounting understanding, while the emotional intelligence and spiritual intelligence variables demonstrated a positive and significant impact on accounting comprehension.